Superconvergence relations in γN→πΔ(1236) - Kloet, W. M.; Ragusa, S. (Elsevier, 1970)
Superconvergent amplitudes involving the isovector part of the photon in the process γN→πΔ(1236) are investigated. Assuming SU(3) symmetry for the ΔΔγ vertex, a relation is obtained between the ΔΔπ and NNπ couplings, which is consistent with the SU(6) limit. For the physical masses of Δ and N this results in gΔ++Δ++πo≈36. © 1970.